HUBUNGAN PENDIDIKAN KESEHATAN PROTOKOL KESEHATAN DENGAN PENERAPAN PENCEGAHAN PENULARAN COVID-19 DI KAMPUNG PICUNG RT 003 RW 05 - Junita Anggi Saputri; Nining Sriningsih; Zahrah Maulidia Septimar (Nusantara Hasana Journal, 2021)
Health education, health protocols are needed as an effort to prevent the transmission of covid-19.The government stanted that all provinces in Indonesia had recorded COVID-19 cases. One of the provinces with high corfirmed cases is East Java 12.695, DKI Jakarta 11.823 south Sulawesi 5.379 Central Java 4.159 and west Java 3.280 task force from 34 provinces has the most recovered cases 6.871 East Java Province 4.391 south Sulawesi 1.941 west Java 1.665 Central Java.1.57. Purpose: to find out the relationship between health education health protocols and the implementation of covid-19 prevention. Research Design: correlation method with cross sectional approach. Samples were taken using the Slovin formula with a total sample of 109 respondents. Sampling using accidental sampling technique. This analysis uses univariate and bivariate analysis with chi square test and correlation.. Results: based on univariate results, the majority of 109 people with good health protocol health education were 87 people (79.8%) and the implementation of good Covid-19 transmission prevention was 92 people (84.4%). The results of the bivariate analysis obtained a p-value of 0.001, so it can be concluded that there is a relationship with health education health protocols on the implementation of preventing Covid-19 transmission. Conclusion: there is a relationship between health education and the implementation of Covid-19 transmission prevention. Suggestion: for the community of Kampung Picung RT 003 RW 05 it can be used as input in increasing public knowledge about the importance of health education protocol health on the implementation of prevention of transmission of Covid-19 in Kampung Picung RT 003 RW 05.